Impact on cardiovascular risk follow-up from a shift to the CKD-EPI formula for eGFR reporting: a cross-sectional population-based primary care study - Van Gelder, V; Scherpbier-De Haan, N; De Grauw, W; O'Callaghan, C; Wetzels, J; Lasserson, D (BMJ Publishing Group, 2013)
OBJECTIVE: To assess the impact on cardiovascular risk factor management in primary care by the introduction of chronic kidney disease epidemiological collaboration (CKD-EPI) for estimated-glomerular filtration rate (eGFR) reporting. DESIGN AND SETTING: Cross-sectional study of routine healthcare provision in 47 primary care practices in The Netherlands with Modification of Diet and Renal Disease Study eGFR reporting. METHODS: eGFR values were recalculated using CKD-EPI in patients with available creatine tests. Patients reclassified from CKD stage 3a to CKD stage 2 eGFR range were compared to those who remained in stage 3a for differences in demographic variables, blood pressure, comorbidity, medication usage and laboratory results. RESULTS: Among the 60 673 adult patients (37% of adult population) with creatine values, applying the CKD-EPI equation resulted in a 16% net reduction in patients with CKD stage 3 or worse. Patients reclassified from stage 3a to 2 had lower systolic blood pressure (139.7 vs 143.3 mm Hg p<0.0001), higher diastolic blood pressure (81.5 vs 78.4 mm Hg p<0.0001) and higher cholesterol (5.4 vs 5.1 mmol/L p<0.0001) compared to those who remained in stage 3a. Of those reclassified out of a CKD diagnosis 463 (32%) had no comorbidities that would qualify for annual CVD risk factor assessment and 20 (12% of those with sufficient data) had a EuroSCORE CVD risk >20% within 10 years. CONCLUSIONS: Use of the CKD-EPI equation will result in many patients being removed from CKD registers and the associated follow-up. Current risk factor assessment in this group may be lacking from routine data and some patients within this group are at an increased risk for cardiovascular events.